Design Build a 4x4 Mimo Microstrip Antenna with Artificial Dielectric Muse Array Technique to increase Antenna Gain pexisting Application 5G - Handayani, Ade Silvia; Sugiyanto, Aan; Ciksadan, Ciksadan; Endri, Jon (Program Studi Teknik Elektro Universitas Khairun, 2023)
The development of fifth-generation cellular technology, commonly referred to as